The Factors Affective to Economic Growth since 2000 - 2018 in Khammouane Province - VONGKEO, Somphone; CHANTHATHEP, Inkeo; VONGSATHIEN , Somxai; KETKEOPHOMPHONE, Sophaphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
The study on the Effecting of private investment to Economy growth since 2000-2018 in Khammoun Province, Lao PDR has the following purposes: (1) to study the general background of Economy in Khammoun Province since 2000-2018, (2) to study the factors effecting to economic growth in Khammoun Province since 2000-2018, by using time series data all 19 years, The key survey tools used in this study are questionnaires by using Quantitative Analyzes, which used Ordinary Least Squares (OLS) in STATA program for panel methodology analyze. For the result of study in the value of public investment in Khammoun Province since 2000-2018 showed that the value of public investment number perpetually decreased by the number in the year 2000 the value of public investment is 161.205 billion kip, in 2001 the value of investment decrease to 8.985 billion kip compared with the year 2000 from 161.205 billion kip in 2000 to 152.220 billion kip in 2001 and withal probably decrementing every year, in 2002 the value of public investment is 142.095 billion kip, 134.240 billion kip in 2003 and only 116.743 billion kip in 2004, the lowest value of public investment in Khammoun province is in year 2007-2008, the value is only 35.533 billion kip and the value of private investment with covered national and international investment since 2000-2018 perpetually incrementing, which 2000 the value of private investment is 127.95 billion kip and probably incrementing every year, for the efficacious of private investment to economy magnification found that both privet and public investment effect to economy magnification in Khammoun Province with confidence level of 98% and the negative relationship with the hypothesis set afore the when the incrementing of the value of private and public investment made the decrementing of the economy magnification.